2017
DOI: 10.1039/c7an00568g
|View full text |Cite
|
Sign up to set email alerts
|

ProxyPhos sensors for the detection of negatively charged membranes

Abstract: Membrane-embedded negatively charged phospholipids (MENCP) can be used as biomarkers for a range of biological processes, including early detection of apoptosis in animal cells, drug-induced phospholipidosis, and selective detection of bacterial over animal cells. Currently, several technologies for the detection of apoptosis and bacterial cells are based on the recognition of MENCPs, including the AnnexinV stain and PSVue™ probes. As probes, these technologies have limitations, the most significant of which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…This would greatly decrease the internalization of the nanoparticles by the mammalian cells because of their negatively charged cell membranes. 38 Furthermore, the FT-IR spectrum of Ag@ MON-AE showed the characteristic absorption bands of ceftazidime at 3416, 1756, 1619, 1537, 1365, 1186, and 1155 cm −1 , further demonstrating the successful loading of the drug in the silver nanoparticles (Figure 2c). 39 Briefly, the strong absorption bands at 3416, 1756, and 1619 cm −1 stand for the −OH group, stretching vibration of CO and CN, and vibration of the NH 2 and NH groups, respectively; the deformation band at 1612 cm −1 indicates the vibration of the The characteristic FT-IR absorption bands of the nanoparticles at different stages demonstrated that the silver nanocomposites were successfully loaded with alginate lyase and ceftazidime (Table S1).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This would greatly decrease the internalization of the nanoparticles by the mammalian cells because of their negatively charged cell membranes. 38 Furthermore, the FT-IR spectrum of Ag@ MON-AE showed the characteristic absorption bands of ceftazidime at 3416, 1756, 1619, 1537, 1365, 1186, and 1155 cm −1 , further demonstrating the successful loading of the drug in the silver nanoparticles (Figure 2c). 39 Briefly, the strong absorption bands at 3416, 1756, and 1619 cm −1 stand for the −OH group, stretching vibration of CO and CN, and vibration of the NH 2 and NH groups, respectively; the deformation band at 1612 cm −1 indicates the vibration of the The characteristic FT-IR absorption bands of the nanoparticles at different stages demonstrated that the silver nanocomposites were successfully loaded with alginate lyase and ceftazidime (Table S1).…”
Section: Resultsmentioning
confidence: 88%
“…Although the drug loading did not significantly change their diameter, the ceftazidime package greatly reduced the zeta potential of the nanoparticles from 30.06 to 7.09 mV (Figure a,b). This would greatly decrease the internalization of the nanoparticles by the mammalian cells because of their negatively charged cell membranes . Furthermore, the FT-IR spectrum of Ag@MON-AE showed the characteristic absorption bands of ceftazidime at 3416, 1756, 1619, 1537, 1365, 1186, and 1155 cm –1 , further demonstrating the successful loading of the drug in the silver nanoparticles (Figure c) .…”
Section: Resultsmentioning
confidence: 94%
“…In addition, the ligation of negatively charged Cy5.5 on the proteins further lowered electric charges of the MamC-HAF-or MamC-THAFmodified magnetosomes (Figure 2c). Considering the negatively charged membranes of mammalian cells, 35 this could significantly reduce the nonspecific binding of bacterial nanoparticles to normal cells, 36 which is necessary for imaging agents in clinical applications. In addition, the presence of MamC-HAF or MamC-THAF on the magnetosomes was further confirmed by SDS-PAGE.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several different fluorescence activation strategies have been explored that target intracellular or extracellular cell death biomarkers. 1718 In the specific case of “turn-on” fluorescent probes that target exposed PS, there are published cell studies using visible wavelength dyes, 19 or probes that exploit concentration dependent aggregation effects, 2021 but no demonstration of utility for in vivo imaging ( i.e. , imaging of the dead/dying cells in a living subject).…”
Section: Introductionmentioning
confidence: 99%